A comparative analysis of the time-dependent magnetized blood-based nanofluids flows over a stretching cylinder. Issue 4 (April 2023) - Lone, Showkat Ahmad; Anwar, Sadia; Saeed, Anwar; Seangwattana, Thidaporn; Kumam, Poom; Kumam, Wiyada
Abstract: This article explores the analysis of magnetized blood-based nanofluids flows over an extending cylinder. The nanofluid contains copper, copper oxide and iron oxide nanoparticles which are mixed with blood. The mathematical model has been built-up in partial differential equations (PDEs) form and then changed into ordinary different equations by mean of suitable similarity variables and then has been evaluated by homotopy analysis method (HAM). The convergence of the applied technique is presented in graphical form. During the solution process, the influences of physical parameters like magnetic parameter, unsteadiness parameter, curvature parameter and thermal relaxation time parameter on the flow profiles have been investigated and depicted in Figures and Tables. The correctness of the present model has also been presented in tabular form. The results show that the greater curvature factor reduces the radius of cylinder due to which thickness of layer becomes thin at the boundaries and therefore the velocity distribution declines, while the greater curvature parameter has the increasing impact on the temperature distribution for constant wall temperature (CWT) case and decreases the temperature distribution for prescribed surface temperature (PST) case.